Journal of Statistical Physics - Biroli, Giulio; Carlen, Eric.; Giardina, Irene; Dhar, Abhishek; Giuliani, Alessandro; Tasaki, Hal.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The Journal of Statistical Physics publishes original and invited review papers in all areas of statistical physics as well as in related fields concerned with collective phenomena in physical systems.
Keywords: Physical chemistry; Physics; Quantum physics; Statistical Physics and Dynamical Systems; Theoretical, Mathematical and Computational Physics; Physical Chemistry; Quantum Physics